1990
DOI: 10.1177/146642409011000212
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Patients in an Indian Hospital

Abstract: The study was carried out at the Emergency Department of Jawaharlal Nehru Medical College Hospital, Aligarh Muslim University, Aligarh, India, to ascertain the pattern of trauma in the patients. A total of 2446 trauma cases were recorded in the year 1987. Accidental falls were the commonest cause of injury, i.e 35.7%, followed by motor-vehicle collisions (23.5%), pedal cyclists (8%), occupational injuries (5.2%) and sports injuries (5.2%). The commonest age group involved was 5-15 years which accounted for 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The median incidence of fall injury in Asia in those aged 0–18 years was found to be 170 per 100 000 children averaging 43% of all injuries (Table S2) (see Tables S1 and S2 for citation of references 14–55). Among those less than 5 years in Asia there was a median incidence of 58.2 falls per 100 000 children, comprising 35% of all injuries.…”
Section: Resultsmentioning
confidence: 99%
“…The median incidence of fall injury in Asia in those aged 0–18 years was found to be 170 per 100 000 children averaging 43% of all injuries (Table S2) (see Tables S1 and S2 for citation of references 14–55). Among those less than 5 years in Asia there was a median incidence of 58.2 falls per 100 000 children, comprising 35% of all injuries.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of anatomical location of road traffic injuries shows that 60% of the victims have injuries to the extremities; head and facial injuries are noted in 30-60% of the injured and 25-80% of the dead victims. Many studies have also shown that fractures and superficial or open wounds are a common occurrence [15,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…T rauma constitutes a major health concern in developed nations; however, an increasing awareness of the trauma burden in developing countries has led many to consider it a global epidemic, with 90% of fatalities occurring in lowand middle-income countries. [1][2][3][4] More specifically, rural trauma has different connotations than urban trauma and has lead some to regard it as a challenge in the care of the injured patient in this decade. 5 In 2003, national statistics in Ecuador showed that the fatality rate from trauma (motor vehicle collisions and aggressions combined) was 29.5 per 100,000 inhabitants, representing one of the leading causes of mortality.…”
mentioning
confidence: 99%